Physical exercise and cognitive training interventions to improve cognition in hemodialysis patients: A systematic review - Bogataj, Špela; Mesarič, Katja Kurnik; Pajek, Maja; Petrušič, Tanja; Pajek, Jernej (Frontiers in Public Health, 2022)
Introduction Patients with chronic kidney disease treated with hemodialysis (HD) have lower cognitive abilities compared to the age-matched healthy population. Recently, physical exercise and cognitive training have been presented as possible interventions to improve cognitive abilities both in the general population and in patients with chronic diseases. To date, there is no general overview of the current knowledge on how these interventions affect cognitive abilities in HD patients and what tests are used to measure these effects. Methods Three electronic databases were searched for randomized controlled studies of physical exercise or cognitive training interventions that examined effects on cognitive abilities/performance in HD patients. Results Six articles were included. All included studies used physical exercise as an intervention, with one study also including tablet-based cognitive training. Four studies included an intradialytic approach and two included a home-based intervention. Intervention lasted. A significant intervention effect was observed in three studies compared with the control condition. Conclusion The present review suggests that physical exercise might improve or at least not worsen cognitive performance in HD patients, whereas the effect of cognitive training has not yet been adequately studied. There is a need for more sensitive and specific cognitive tests to adequately measure the effects of interventions in the HD population.